Increasing Students' Grammar Performance through Communicative Language Teaching - Marzuki, Mutmainnah; Emirati, Emirati; Syam, Nur Ina (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The aim of this research is to determine the effectiveness of grammatical practice activities in the CLT method in increasing the grammar capability of the second semester students at University of Muhamamdiyah Bulukumba. Based on the research objective, the researcher would like to find out how the CLT method is being used effectively and efficiently in the EFL class through grammar practice activities. The design of the research is a classroom action research (CAR). The researcher acts and follows four steps: Planning, Implementing of the action, observation and evaluation. The study's participants were second-semester English Education students at the University of Muhammadiyah Bulukumba. There were two classes, 20A and 20B, each with 21 students and 30 students, for a total of 51 students. The research sample was drawn from class 20A, which consisted of 21 students, using a random sampling technique. In the collection of the data, the researcher used certain types of instruments; 1) pre-test and post-test testing, questionnaire, 3) Grammar Practice Activities materials. The researcher concluded that the Grammar Practice Activities, as one of the applications of the CLT method, were effective in increasing the grammar ability of the second semester students at the University Muhammadiyah of The data collected before and after the treatment in every circle has verified this. The Grammar Practice Activities was proven to increase the students’ interest and involve the students as a center in teaching learning process toward English grammar